PENGEMBANGAN MEDIA PEMBELAJARAN ULAR TANGGA SMART UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SEKOLAH DASAR KELAS I - Lutfiana, Ovi Dwi; Kurnia, Ita; Wahyudi, Wahyudi (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research was conducted to develop a smart snakes and ladders learning media aimed at improving the learning outcomes of first-grade students. The study was designed to assess the validity, practicality, and effectiveness of using the snakes and ladders media in teaching. The research method applied is research and development using the ADDIE model, which consists of five steps: analysis, design, development, implementation, and evaluation. The analysis techniques used are (1) validity testing, (2) practicality testing, and (3) effectiveness testing. Based on the research, the results are as follows: (1) the scores from content and media experts were 88%, (2) limited trial responses showed 86% from teachers and 89% from students, (3) a limited scale evaluation yielded 85% with an effective category, and a broader scale evaluation resulted in 86%. These results demonstrate that the developed smart snakes and ladders learning media can positively influence the learning outcomes of students at SDN 1 Ngadi.